ONLINE MARKETING STRATEGY ON SMALL AND MEDIUM MICRO ENTERPRISES (MSMEs) KERUPUK MELARAT IN SINARMUKTI VILLAGE - Yuniarsih Yuniarsih; Rizky Ariansyah Siregar; Nurrohman Nurrohman; Anton Nasrullah; Mutia Anjani; Iim Soimin; Rani Puspa (International Journal of Engagement and Empowerment, 2021)
Business actors must have the ability to manage online marketing. Social media as a marketing tool aims to expand the reach of consumers in various cities to increase sales of Small and Medium Micro Enterprises (MSMEs) "Kerupuk Melarat" in the village of Sinarmukti. The problem faced by business actors is the lack of the ability to conduct promotions online. The method of this activity is through socialization training for business actors on how to use social media to promote products to consumers. The purpose of this activity is to improve the ability of business actors to manage online product marketing and increase sales. The result of this program of activities is to increase business actors' ability to implement and manage online advertising and marketing programs and make it easier for consumers to find their needs.